2023
DOI: 10.1186/s12978-022-01525-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the WHO Labour Care Guide to reduce the use of Caesarean section in four hospitals in India: protocol and statistical analysis plan for a pragmatic, stepped-wedge, cluster-randomized pilot trial

Abstract: Background The World Health Organization (WHO) Labour Care Guide (LCG) is a paper-based labour monitoring tool designed to facilitate the implementation of WHO’s latest guidelines for effective, respectful care during labour and childbirth. Implementing the LCG into routine intrapartum care requires a strategy that improves healthcare provider practices during labour and childbirth. Such a strategy might optimize the use of Caesarean section (CS), along with potential benefits on the use of oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Nine ongoing or planned research efforts were identified (Additional file 1: Table S8), mainly responding to the second priority to improve understanding of the effect of WHO LCG on maternal and perinatal outcomes, and the process and experience of labour and childbirth care [24][25][26][27][28]. One completed, but noy yet published study in India was identified under the theme "optimize implementation".…”
Section: Phase 3: Consensus-buildingmentioning
confidence: 99%
“…Nine ongoing or planned research efforts were identified (Additional file 1: Table S8), mainly responding to the second priority to improve understanding of the effect of WHO LCG on maternal and perinatal outcomes, and the process and experience of labour and childbirth care [24][25][26][27][28]. One completed, but noy yet published study in India was identified under the theme "optimize implementation".…”
Section: Phase 3: Consensus-buildingmentioning
confidence: 99%
“…(28,29) The trial protocol was pre-registered (CTRI/2021/01/030695), with the protocol and statistical analysis plan published prior to trial closure; there were no major deviations or changes. (30) We sought permission from the head of study hospitals (gatekeepers) and individual providers before commencing the trial. The study protocol specified a waiver of individual consent for data collected on women giving birththese data were non-identifiable, routinely-collected clinical variables in medical records and labour ward registries.…”
Section: Trial Approvals and Oversightmentioning
confidence: 99%
“…This recommendation was made with anticipation that the new tool was easy to use, promptly identifies deviations from normal through regular assessments, encourages self-efficacy, stimulates HCP interaction and shared decision-making, recognises participation of labour companions to promote women-centred care, but importantly the LCG has been developed for HCPs to identify deviations from normal through regular monitoring and assessment of women and their unborn babies. Based on pilot studies, this LCG has been suggested to facilitate HCPs to quickly identify any deviation from normality and thus improve labour monitoring as well as the well-being of women and their babies in comparison with the partograph 15 16. The LCG also has been suggested to encourage interaction between the healthcare team, women and labour companion or family members, while emphasising safety and providing the needed supportive care for the expectant women in our setting 17.…”
Section: Introductionmentioning
confidence: 99%
“…The LCG also has been suggested to encourage interaction between the healthcare team, women and labour companion or family members, while emphasising safety and providing the needed supportive care for the expectant women in our setting 17. In fact, according to Vogel and colleagues, this new WHO LCG monitoring tool is regarded as the ‘next-generation’ partograph incorporating recent effective intrapartum care guidelines 18 19. When used properly, the LCG is thought to accurately detect prolonged labour in time for HCPs to avoid unnecessary practices and interventions, and perform required interventions in time before progressing to obstructed labour and its sequelae, such as ruptured uterus, postpartum haemorrhage, sepsis, maternal and neonatal deaths.…”
Section: Introductionmentioning
confidence: 99%